Troglomorphic features of Astroblepus pholeter, a cavefish from Ecuador, and possible introgressive hybridization - Luis Espinasa; Jenna Robinson; Daphne Soares; Geoffrey Hoese; Theofilos Toulkeridis; Rickard Toomey III (Subterranean Biology, 2018)
Cave organisms are often characterized by reduced pigmentation, eyesight, and enhanced mechanosensory functions. The stygobitic catfish Astroblepus pholeter is found within some subterranean drainages in Ecuador. The species was first described in 1962 with specimens that were all highly depigmented and troglomorphic. The next observations in the field occurred until 2011, 2015 and 2018. At such dates, specimens examined progressively displayed more surface-like appearance. Appendages in these individuals were progressively shorter and pigmentation levels are now as high as some surface Astroblepus. Based on sampled specimens, it would appear that since 1962, the population has been progressively composed of less troglomorphic individuals. One possibility is that the population has undergone introgressive hybridization in recent years as surface Astroblepus are known to enter the caves and cohabitate with the troglomorphic Astroblepus. Lastly, we report that Individuals are able to detect and respond to light. Histological analyses show that A. pholeter’s eyes have all of the major ocular structures (lens, optic nerve, and all retinal layers).